The Effect of Internal Control System on the Financial Performance of SACCOS in Rukiga District: A Case study of Rukiga SACCO in Rukiga District. - Katwesigye, Joshua (Kabale University, 2023)
The study was about 'the effect of the internal control system on the financial performance of SACCOs in Rukiga District. The study was guided by objectives namely; to establish the types of internal control systems that is being used by Rukiga SACCO in Rukiga District, to establish the relationship between the internal control systems and financial performance of Rukiga SACCO in Rukiga District, and to find out the factors that affects financial performance of SACCOs in Rukiga District. A descriptive research design was used in the study. The researcher used both Primary and secondary data. Secondary data was collected from the Sacco financial statements and policies. Literature was reviewed using secondary data sources including other dissertations, journals, Sacco's financial reports, SME's Act, Sacco supervision annual report, internet, research projects, and information from the university library. The study also found that control activities and the monitoring of controls in an organization basically comprise. Some respondents showed that control environment factors include; integrity and ethical values of personnel responsible for creating, administering, and monitoring the controls commitment and competence of persons performing assigned duties, board of directors, or audit. Some respondents showed that internal control is heavily dependent on a well-documented and communicated organizational structure that clearly shows lines of reporting responsibility and authority and provides effective communication throughout the organizational/SACCO. Capital for some customers affects the finances of Rukiga Sacco as the customers don't have enough money to save. Even the Sacco itself may not have enough starting capital maybe to start some branches. Profitability also influences the financial performance of SACCO. The study concludes that it will be said that the financial management of any organization cannot do without internal control as true and fair presentation of financial statements may never be possible if the board and senior management are not committed to providing a well-planned internal control system. The study recommends that the management of Rukiga Sacco should design effective internal control systems by ensuring that adequate asset listings is done by management, capital assets purchased are approved by appropriate level of management and asset numbering is done to show location and protection of the assets. Management should ensure that there are adequate organizational controls and that each staff knows his duties and equally ensures effective segregation of duties. The internal control system should be remolded and strengthened to position the staff in carrying out their duties efficiently and effectively and at the same time evaluated periodically to strengthen its weaknesses in the organization.